Draft biennial programme of regional and international cooperation activities of the Statistical Conference of the Americas of ECLAC, 2007-2009 (ECLAC SantiagoCL, 2007)
Presents for adoption the strategic plan 2005-2015 which defines the mission, vision, strategic goals, specific goals and principal lines of action on which the Conference should focus its work during the period ending in 2015.
Keywords: STATISTICAL SERVICES